The criteria used by private general practitioners in Bloemfontein for the diagnosis and referral of asthma patients aged 6-15 years - Monia Balt; Caroline Joubert; Michelle Nel; Lincoln J. Solomon; Gina Joubert (AOSIS, 2010)
Background: Participants in the study were general practitioners (GPs) in private practice in Bloemfontein, South Africa. Objectives: To determine and evaluate the criteria employed by GPs in Bloemfontein to diagnose and refer chronic and acute asthma patients aged 6-15 years and to investigate the actual diagnostic criteria used by GPs, as compared to the theoretical (i.e. textbook) criteria. Method: A descriptive study was performed. A questionnaire was designed to investigate which methods of diagnosis were employed by GPs with regard to childhood asthma. The questionnaire was distributed to GPs who fulfilled certain inclusion criteria and were selected by means of simple random sampling. Statistical analysis of data was done by the Department of Biostatistics, University of the Free State, and results were summarised as frequencies and percentages. Results: Certain elements were lacking with regard to the patients' histories taken by GPs. These included severity and frequency of attacks, as well as precipitating factors, such as smoking in the family and allergies. A worrisome number of GPs did not seem to be aware of the exact clinical picture of asthma in children and some failed to use the prescribed guidelines proposed for diagnosis of this condition in young patients. Most GPs indicated that they refer asthmatic children to private specialists, although this practice depended on the medical aid status of the patient's parents/guardian. Conclusion: As portrayed by the feedback obtained from these Bloemfontein-based GPs, it could be presumed that the diagnosis of asthma in children did not always meet the standard criteria.